Advancing the additive manufacturing of PLA-ZnO nanocomposites by fused filament fabrication - Wei Juene Chong; Dejana Pejak Simunec; Adrian Trinchi; Ilias (Louis) Kyratzis; Yuncang Li; Paul Wright; Shirley Shen; Antonella Sola; Cuie Wen (Virtual and Physical Prototyping, 2024)
ABSTRACTPoly(lactic acid)-zinc oxide (PLA-ZnO) nanocomposites for fused filament fabrication have potential applications in the biomedical field as they combine the bio-compatibility of PLA with the antibacterial properties of ZnO. This work investigates the effects of masterbatch mixing strategy, ZnO concentration and ZnO surface treatment (silanisation) on the printability and the mechanical performance of the nanocomposites as a pre-requirement to the wider uptake of these materials. The results showed that the printability decreased as the filler loading increased. However, the surface treatment of the ZnO powder enhanced the matrix-filler interfacial interactions and reduced the thermal degradation of PLA. This ameliorated the printability and the tensile properties of the nanocomposites filled with up to 5 wt.% of ZnO. Moreover, despite the additional thermal treatment, melt-mixing prevented the degradative effect induced by the solvent used for solvent mixing. Future work will focus on assessing the antibacterial properties of the nanocomposite FFF parts.